Labour law reforms in Europe: adjusting employment protection legislation for the worse? - Schömann, Isabelle (Brussels, 2014)
" This new working paper is intended to map reforms of employment protection law in the member states with the aim of addressing these legal changes in the context of the crisis, but also in the context of the deregulation agenda of the European Commission.